Novel structural-related analogs of PFI-3 (SRAPs) that target the BRG1 catalytic subunit of the SWI/SNF complex increase the activity of temozolomide in glioblastoma cells. (1st January 2022) - He, Yali; Yang, Chuanhe; Wang, Yinan; Sacher, Joshua R.; Sims, Michelle M.; Pfeffer, Lawrence M.; Miller, Duane D.
Graphical abstract: Abstract: Glioblastoma (GBM) is the most aggressive and treatment-refractory malignant adult brain cancer. After standard of care therapy, the overall median survival for GBM is only ∼6 months with a 5-year survival <10%. Although some patients initially respond to the DNA alkylating agent temozolomide (TMZ), unfortunately most patients become resistant to therapy and brain tumors eventually recur. We previously found that knockout of BRG1 or treatment with PFI-3, a small molecule inhibitor of the BRG1 bromodomain, enhances sensitivity of GBM cells to temozolomide in vitro and in vivo GBM animal models. Those results demonstrated that the BRG1 catalytic subunit of the SWI/SNF chromatin remodeling complex appears to play a critical role in regulating TMZ-sensitivity. In the present study we designed and synthesized S tructurally R elated A nalogs of P FI-3 (SRAPs) and tested their bioactivity in vitro . Among of the SRAPs, 9f and 11d show better efficacy than PFI-3 in sensitizing GBM cells to the antiproliferative and cell death inducing effects of temozolomide in vitro, as well as enhancing the inhibitor effect of temozolomide on the growth of subcutaneous GBM tumors.